2019
DOI: 10.1039/c8gc03666g
|View full text |Cite
|
Sign up to set email alerts
|

Terephthalic acid from renewable sources: early-stage sustainability analysis of a bio-PET precursor

Abstract: The present work compares, from a life cycle perspective, four different ways for the production of terephthalic acid.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
54
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(55 citation statements)
references
References 35 publications
1
54
0
Order By: Relevance
“…It is therefore necessary to verify the environmental sustainability of biobased and CO 2 -based solutions using quantitative evaluations, such as life cycle assessment (LCA). For example, a comparison of biobased TPA (produced from corn, sugarcane and orange peel) and TPA produced from oil [ 24 ] revealed that first-generation raw materials (corn and sugarcane) had a similar environmental impact to oil, mainly due to the depletion of resources and the extra land required for crop cultivation. In contrast, the biobased route involving second-generation materials, specifically the upcycling of side-streams such as orange peel, achieved the most sustainable solution with the lowest environmental impact because it did not involve resource extraction or land use and made use of resources that would otherwise be wasted.…”
Section: Production Phasementioning
confidence: 99%
“…It is therefore necessary to verify the environmental sustainability of biobased and CO 2 -based solutions using quantitative evaluations, such as life cycle assessment (LCA). For example, a comparison of biobased TPA (produced from corn, sugarcane and orange peel) and TPA produced from oil [ 24 ] revealed that first-generation raw materials (corn and sugarcane) had a similar environmental impact to oil, mainly due to the depletion of resources and the extra land required for crop cultivation. In contrast, the biobased route involving second-generation materials, specifically the upcycling of side-streams such as orange peel, achieved the most sustainable solution with the lowest environmental impact because it did not involve resource extraction or land use and made use of resources that would otherwise be wasted.…”
Section: Production Phasementioning
confidence: 99%
“…The major influencing factors for the development of bio-based plastics are the technological barriers that must be overcome in order to reach a large-scale production, the suitability of these materials to be used as bulk materials, their competitiveness in terms of cost with respect to petroleum-derived ones and the availability of raw materials for their synthesis. A very interesting paper is that of Volanti et al [75], which reports a sustainable analysis used to estimate the environmental performance of three routes followed to obtain bio-PTA for the synthesis of bio-PET: from sweet corn, from sugar beet and maize grain, and from orange peels. The results were compared with traditional technology.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, it is interesting to note that the advantageous barrier properties of PEF over PET are most commonly underlined in the introductory sections of any new scientific publication or other communications related to PEF, and this review is no exception. This is definitely a very heavy argument in favor of PEF which, in addition to its renewable-based origin and its favorable atomic balance (i.e., C 6 sugars give C 6 FDCA) could make a clear-cut difference compared with e.g., bio- PET (Volanti et al, 2019 ) and other biobased polyesters such as PLA or PBS, although bioeconomic aspects will lead this fight in the end.…”
Section: Structure-properties Relationshipsmentioning
confidence: 99%